Incidence and Predictors of Anemia Among Pregnant and Non-Pregnant Women Attending Antenatal Clinics in the Kurdistan Region of Iraq - Ali, Himan I.; Ibrahim, Balqees; Ahmad, Shana; Rasheed, Aronk; Hazim, Leva (Technium BioChemMed, 2024)
Introduction: The burden of anemia during pregnancy is a global concern in the field of healthcare. Struggling economies such as Iraq are the most affected by this burden. The actual instances of anemia differ depending on the underlying socio-demographic factors. Nonetheless, anemia in pregnancy is one of the causes of poor health and mortality, especially for pregnant women. Methodology: A cross sectional analysis was used among 153 pregnant women and 153 non-pregnant women attending antenatal clinics in Kurdistan region, Iraq. The dependent variable used in the study was the occurrence of anemia during pregnancy via the levels of Hb, RBC, MCV, and MCH. Data was gathered using questionnaires and face-to-face interviews. Blood sample data was also collected to test the levels of the four parameters (Hb, RBC, MCV, and MCH). Statistical analysis was applied in determining the occurrence of anemia, with logistics regression being perform using IBM Statistics to determine the triggers of anemia during pregnancy. Results: The descriptive statistics for pregnant women, found that the mean and standard deviations for key blood parameters are: Hb (M=12.02±SD=1.330), RBC (M=4.26±SD=0.522), MCV (M=82.91±SD=8.151), and MCH (M=28.43±SD=4.638). The normal/abnormal categories, the results were as follows: RBC (normal = 96.1%, abnormal = 3.9%), Hb (normal = 64.1%, abnormal = 35.9%), MCV (normal = 85%, abnormal = 15%), and MCH (normal = 86.9%, abnormal = 13.1%). Furthermore, the descriptive statistics for non-pregnant women, found that the mean and standard deviations for key blood parameters are: Hb (M=13.23±SD=0.937), RBC (M=4.59±SD=0.367), MCV (M=83.65±SD=2.978), and MCH (M=29.19±SD=1.430).The normal/abnormal categories, the results were as follows: RBC (normal = 97.4%, abnormal = 2.6%), Hb (normal = 75.8%, abnormal = 24.2%), MCV (normal = 90.8%, abnormal = 9.2%), and MCH (normal = 90.10%, abnormal = 9.90%). Conclusion: There is a significant difference in the results for pregnant and non-pregnant women in the mean blood parameters (MCV, MCH, Hb, and RBC) during pregnancy. Specifically, the study found that the level of Hb varies significantly between the two study participants. Hb scores are also higher among non-pregnant women than pregnant women. Additionally, RBC, MCV, and MCH levels are higher for non-pregnant women than for pregnant women. Anemia is linked with factors such as occupation, age, obstetrical history of stillbirth, abortion, parity, and gravity on the potential of developing anemia during pregnancy.